Effect of Salt Solution Combined with Blanching on Color Retention and Antioxidant Activity in Dried Wolffia (Wolffia arrhiza) - Doungtip, Peerarat; Srisorn, Paphakorn; Hunsakul, Kanrawee (Journal of Food Technology, Siam University, 2025)
The objective of this research was to study the effect of salt solution combined with blanching on color retention and antioxidant activity in dried Wolffia using a hot air dryer. Four types of salt solutions were used such as NaCl 1% (w/v), MgSO4 0.1% (w/v), CaCl2 0.1% (w/v) and ZnSO4 0.1% (w/v). The Wolffia was pre-treated with blanching (80ºC, 3 min) in the different salt solutions before drying in a hot air oven at 60ºC for 8 hrs. The results showed that physical properties, color values, total phenolic content, antioxidant activity, and chlorophyll content of pre- treated dried Wolffia were significantly different (p<0.05), compared with the conventional method. Among all treatments, the use of MgSO4 salt could retain the Wolffia color, chlorophyll content, and present a high antioxidant activity. The L*, a* and b* values of Wolffia that pre-treated with MgSO4 salt were 37.11, -3.21 and 22.09, respectively. The total chlorophyll was 627.63 mg/100g DW. The amount of antioxidants from DPPH and FRAP method were 11.64 and 22.55 mmol Trolox eq/kg, respectively and total phenolic content was 454.26 mg GAE/100 g.